THE LECTOTYPE AND TYPE LOCALITY OF CANDOIA CARINATA (REPTILIA, SERPENTES) - Bohme, Wolfgang; Smith, Hobart M.; Rybak, John; Van Breukelen, Frank; Chiszar, David (Contemporary Herpetology, 1998)
The lectotype of Boa carinata Schneider, 1801, has been rediscovered and is now ZMFK 35503, having been transferred in 1977 from the Göttingen Museum, its original location. Its type locality has not been reported previously, but is indicated as “Amboina” on a label with the lectotype. The specimen is redescribed and fi gured, and conforms with expectations for material from the vicinity of the type locality. A brief history of Schneider and of the syntypes of Boa carinata, now Candoia carinata, is reviewed.